The Influence Of Work Environment And Workload On The Performance Of Pamong Praja Police Unit Employees - Lutfi Faujiah; Aji Tuhagana; Zenita Apriani (International Journal of Management, Economic, Business and Accounting, 2025)
Purpose of the study — This research aims to examine the influence of the work environment and workload on employee performance at Satpol PP Kab Karawang. Research method— A quantitative approach was employed, utilizing a sample of 52 individuals determined by the Slovin formula. Data analysis was conducted using multiple linear regression, with F-test and t-test at a 5% significance level, processed through SPSS 29. Result— The findings revealed a significant impact of the work environment on employee performance. While workload did not individually affect performance, both factors combined had a significant effect, evidenced by an F score of 7.466, surpassing the critical value of 3.186. The combined influence accounted for 23.4% of the variance in performance. Conclusion— The study concludes that the work environment positively influences employee performance, while workload alone does not. The results suggest that organizations should focus on enhancing the work environment to improve employee outcomes, as other factors may also play a significant role in performance.